(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In modern society, innovations play a significant role in discovering new knowledge through scientific research. Innovations provide effective solutions in economic, social, cultural, and ecological fields, contributing to the development of society. The interconnection between scientific research and innovations, through their practical application, enables sustainable development and the creation of advanced technologies.